ChemInform Abstract: Cu‐Promoted Sydnone Cycloadditions of Alkynes: Scope and Mechanism Studies. Issue 27 (18th June 2015) - Comas‐Barcelo, Julia; Foster, Robert S.; Fiser, Bela; Gomez‐Bengoa, Enrique; Harrity, Joseph P. A.
Abstract The process is significantly accelerated in the presence of copper salts: the reaction time can be reduced from <12h to a few hours or even 20 min.